PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERJUDIAN ONLINE DI MEDIA SOSIAL (Studi Putusan Pengadilan Negeri Medan Nomor 3132/Pid.B/2021/PN Mdn) - Inggrid Rumyriris Sitorus (Universitas Harapan Medan, 2022)
Gambling done via the internet occurs because betting on sports activities or casinos is done via the internet. The research data is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials, which are arranged qualitatively. Law enforcement by the Police against perpetrators of online gambling crimes on social media is based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions to be precise in Article 27 number (2) and for regulation of criminal acts regulated in Article 45 of the Law on Information and Electronic Transactions. Efforts to countermeasures through penalties are carried out by imposing severe penalties on online gambling actors and non-penalists by taking preventive actions or efforts, namely preventing the occurrence of online gambling crimes through social media. Decision Number 3132/Pid.B/2021/PN. Mdn is that there is no basis to abolish the sentence against the defendant so that the defendant is stated to be able to take responsibility for his actions and the defendant is sentenced to imprisonment for 1 (one) year which is lighter than the demands of the public prosecutor who demands that the defendant be given a prison sentence of 1 (one) year. one) year 3 (three) months.